Implementation of Work from Home Policy at PT. Masaji Tatanan Kontainer Indonesia - Chrisyanto, Nadia Shafira; Noviyanti, .; Effendi, Isnaini Fitria (KnE Social Sciences, 2022)
Policy implementation is the process of putting government regulations into effect. The Government issued a policy regarding working from home (WFH) in response to the Covid-19 pandemic. The goal of this study was to describe how the Surabaya Mayor’s Regulation Number 16 of 2020 Regarding Guidelines for Large-Scale Social Restrictions in Handling Corona Virus Disease 2019 were implemented in the city of Surabaya. This article used a qualitative approach and descriptive research methods. George Edward III’s theory, which includes indicators such as communication, resources, disposition, and bureaucratic structure, was the focus of this investigation. Primary and secondary data sources were used to inform the analysis of the WFH policies. The findings of this study revealed that policy communication had dimensions of uneven transmissions due to the division head’s inability to provide details related to the WFH schedule. Also, policy implementers had a lack of understanding of the unclear information. Other challenges included appropriate resources for providing facilities and infrastructure; implementing dispositions in the appointment of a Covid-19 Task Force; providing incentives in the form of subsidies for credit, UHT milk and vitamins for all employees; and changes in bureaucratic structure following WFH policy procedures such as standby on-call and filling in attendance through spreadsheets. We therefore conclude that PT. Masaji Tatanan Container Indonesia, in Greges Jaya, Surabaya needs to evaluate its communications and ensure policy implementers develop their understanding to reduce unclear information in each division of the company. Keywords: policy implementation, work from home, Covid-19